Manajemen Pemanfaatan Google Forms Sebagai Media Kegiatan Belajar Mengajar Peserta Didik Sekolah Dasar : Management of Using Google Forms as a Media for Teaching and Learning Activities of Students at SD Negeri Kembangan Korwil Kapanewon Bambanglipuro Yogyakarta - dewi riska; Welius Purbonuswanto (Media Manajemen Pendidikan, 2022)
Abstract. Management is a process of utilizing human resources through collaboration with other people to achieve certain goals effectively and efficiently which is carried out through planning, planning, organizing, replacing, and controlling actions. During the pandemic, school management must continue to run smoothly. The pandemic has had a major impact on various sectors, one of which is education. The Indonesian government made a policy as an effort to prevent Covid by giving an appeal to the public to always maintain physical distance, avoid all forms of activity in the form of crowds and always maintain cleanliness. Educators must ensure that teaching and learning activities must continue, even though students are at home. Educators are required to design learning media and are expected to have the skills and ability to think creatively and innovatively to collaborate with students during the learning process by utilizing internet technology. There are many choices of media that can be used by teachers during online learning. The applications that are available from free to applications that have to spend a lot of money, one of which is e-Learning using the Google Forms application. Google Forms is part of the Google platform that allows someone to create surveys, questions and answers with online form features that can be made according to their needs. Thus teachers and students can still carry out activities at home to keep communicating and learning. By using internet learning media Google Forms teaching and learning activities for teachers and students must run smoothly because the Google Forms application was chosen as a learning medium and used in history learning because teachers have attended workshops on the use of Google Forms media in learning. The use of these media is also more widely used by teachers than other applications, because of the ease in the process of making and using it. So if there are technical problems with the use, you can ask other teachers who are more familiar with the use of Google Forms.